Land–Air–Wall Cross-Domain Robot Based on Gecko Landing Bionic Behavior: System Design, Modeling, and Experiment - Chengwei Huang (Applied Sciences, 2022)
Based on the bionic behavior of geckos, this paper presents a land–air–wall cross-domain robot which can fly in air, run on the ground, and adhere to various wall surfaces. When geckos jump and adsorb to vertical surfaces such as trunks, they can still adsorb to the wall with a large contact speed. Inspired by this phenomenon, we analyze the mechanism, apply it to our robot, and optimize the design of the robot structure. In addition, geckos use their tails to adjust posture to achieve abdominal landing during the process of falling. Inspired by this phenomenon, based on the rotor lift/power curve, we optimize the center of gravity by controlling the servo angle. The initial center of gravity offset of the robot is estimated by the extended state observer. The method reduces the distance between the center of gravity and the geometric center, balances the load of each propeller, and finally reduces the total power. The experiment and simulation results validate the feasibility of the land–air–wall cross-domain robot and the bionic methods.